Outcomes of Simultaneous Liver–Kidney Transplant Recipients According to Pre-Transplant Transjugular Intrahepatic Portosystemic Shunt (TIPS) in the United States - Tristan Meier; Kathryn Schmidt; Kristin Cole; Jody C. Olson; Timucin Taner; Douglas A. Simonetto; Samy Riad (Transplantology)
Background: Previous data suggested that the outcomes for liver-alone transplant recipients following transjugular intrahepatic portosystemic shunt (TIPS) insertion were comparable to those without TIPS. This study investigates the association between TIPS and outcomes among simultaneous liver–kidney (SLK) recipients in the United States. Methods: Utilizing the Scientific Registry for Transplant Recipients (SRTR) standard analysis file from 2003 to 2022, we examined 9717 adult SLK recipients, among whom 858 had undergone TIPS before transplantation. Kaplan–Meier curves were generated to assess recipient and death-censored liver and kidney graft survival. Mixed-effects Cox proportional hazard models were employed to analyze the association between TIPS and the outcomes of interest, where the transplant center was treated as a random effect. The models were adjusted for recipient age, sex, MELD score, diabetes, duration of listing, induction, steroid maintenance, hepatitis C status, donor age, donor sex, cold ischemia time, local vs. shipped organs, and allocation era. Results: Overall, the two groups were comparable, with minor differences. Notably, the median liver waiting time was significantly longer in the TIPS group compared to the non-TIPS group (4.1 vs. 2 months, p < 0.001). One-year rejection rates for liver and kidney allografts did not differ significantly between groups. Univariable Cox regression analyses demonstrated no association between TIPS and worse outcomes for recipient, liver, and kidney survival (p = 0.65, p = 0.22, and p = 0.54, respectively). TIPS did not emerge as a predictor of recipient or death-censored liver or kidney graft survival in multivariable models. Conclusion: In this extensive national cohort of SLK transplant recipients, pre-transplant TIPS was not linked to adverse outcomes for recipients or their allografts.